INTERESTS, PERCEPTIONS, AND COMMUNICATION PATTERNS OF PRE-SERVICE MATHEMATICS TEACHER IN LANGSA CITY DURING ONLINE LEARNING - Iden Rainal Ihsan; Muhammad Yakob; Ratu Sarah Fauziah Iskandar; Roni Priyanda; Rizki Amalia (Prima: Jurnal Pendidikan Matematika, 2022)
The aim of this study is to determine the interests and perceptions of mathematics education students in Langsa City towards distance learning, then the next is to study and analyze their communication patterns in learning during the Covid-19 pandemic. The method used in the study was an online survey of 114 mathematics education students from two different universities located in Langsa City, Aceh Province, Indonesia. Survey material contains questions and statements related to interests, perceptions, and communication patterns as the main problems in this study. With all the supports and obstacles, student interest in online learning is very low, 84.21% of respondents are not interested. Then, most of them find it difficult to concentrate while following the lesson. Boredom and difficulty finding relevant learning resources are also part of students' perceptions of online learning. Most of them (79.95%) find it difficult to learn, although 70.18% can still understand the learning material. Furthermore, the WhatsApp application (with all its features) is the most widely used medium of communication to support learning activities (71.93%), both for questions and discussions (both with lecturers and peers). Virtual meeting application is the second most used media for communication (28.07%). The pattern of communication in learning activities is dominated by communication between students and groups of students with a frequency level of 67.64%. Furthermore, communication is carried out between lecturers and groups of students and between lecturers and individuals with a frequency of 24.52% and 7.84%, respectively. According to the results of this study, we argue that it is necessary to develop an integrated blended learning design equipped with a directed communication pattern.